2006
DOI: 10.1080/02757540600658807
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of humic acids of the mound of a wood-feeding termite and of the litter directly below in the Amazon river delta

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 17585 In order to determine the role of termites in the recycling of organic matter and in humification processes, organic matter from the mound of a wood-feeding termite (Nasutitermes sp.) and from the litter directly below has been studied in secondary forest on the campus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Jones [7], studying termite tunnelling through treated soil, proposed a similar mechanism to explain why larger groups of termites could tunnel deeper than smaller ones, with relative mortality being lower in larger groups. It was claimed that the larger the group, the more could tasks be shared, giving more individuals at any time the chance to loaf, rather than having to be involved in tunneling and maintenance tasks most of the time, as in small groups [40][41][42][43][44]. Our results have important practical implications, too.…”
Section: /7mentioning
confidence: 81%
“…Jones [7], studying termite tunnelling through treated soil, proposed a similar mechanism to explain why larger groups of termites could tunnel deeper than smaller ones, with relative mortality being lower in larger groups. It was claimed that the larger the group, the more could tasks be shared, giving more individuals at any time the chance to loaf, rather than having to be involved in tunneling and maintenance tasks most of the time, as in small groups [40][41][42][43][44]. Our results have important practical implications, too.…”
Section: /7mentioning
confidence: 81%
“…And preventing the intestinal seeding as well as growth of pathogenic bacteria. There are many health benefits of adding probiotic organisms to the diet whether in a pure form or in the form of traditional fermented and cultured foods [38][39][40][41][42][43][44][45]. Some of the established general and specific health benefits of robotics including suspected role of robotic strains involved are shown in (Table 4).…”
Section: Reported Therapeutic Uses Of Roboticsmentioning
confidence: 99%
“…In Nigeria, it has been reported that in soils with high termite infestation, farmers lose more than 5 t ha À1 of yam due to damage by termites (Atu 1993). However, in the tropics and subtropics, termite has been reported as litter decomposer, and a key player in soil formation (Richard et al 2006;Belyaeva and Tiunov 2010), yet it degrades the soil quality (Devendra et al 1998).…”
Section: Introductionmentioning
confidence: 99%